Association between IL-1β, IL-8, IL-10 and VEGF polymorphisms and risk of odontogenic maxillofacial infections - A. Yu. Adubetskaya; S. A. Schneider; V. O. Ulianov (Kazimierz Wielki University, 2018)
Background. Nowadays it is being reported an increased number of cases of generalization of odontogenic infections which are caused by dental caries, periodontal diseases and other oral diseases. The beginning and progression of diseases depend on individual genetic profile of patient, but data about the role of genetic factors in purulent-inflammatory diseases of maxillofacial area pathogenesis are limited now. The aim of this study was to assess the possible association between IL-1β, IL-8, IL-10 and VEGF polymorphisms and risk of odontogenic maxillofacial infections. Materials and methods 80 patients with odontogenic maxillofacial infection (with and without diabetes mellitus) and 20 donors were examined. All patients' with odontogenic maxillofacial infection groups were operated and received antibiotic and detoxification therapy. Polymorphism in IL-1B +3954C/T (rs1143634), IL-8 -251T/A (rs4073), IL-10 -1082G/A (rs1800896) and VEGF -634 G/C (rs 2010963) were assessed by polymerase chain reaction. Odds ratio (OR) with 95% confidence interval (CI), Chi-square test were used for statistical analyses. Results. No association observed between VEGF -634 G/C polymorphism and risk of odontogenic maxillofacial infections in patient without diabetes mellitus using all the genetic models. In patients with diabetes mellitus observed association between VEGF -634 G/C polymorphism and odontogenic maxillofacial infections in the codominant (OR=0,429, 95%СІ 0,185-0,994, р=0,046), heterozygous (OR=0,167, 95%СІ 0,048-0,574, р=0,004)and recessive (OR=0,194, 95%СІ 0,061-0,619, р=0,005) models. Polimorphism IL-1B +3954C/T increased the risk of odontogenic maxillofacial infections in patient without diabetes mellitus in the codominant (OR=0,059, 95%СІ 0,023-0,151, р